Mapping the ultrafast flow of harvested solar energy in living photosynthetic cells. Issue 1 (December 2017) - Dahlberg, Peter; Ting, Po-Chieh; Massey, Sara; Allodi, Marco; Martin, Elizabeth; Hunter, C. Neil; Engel, Gregory
Abstract Photosynthesis transfers energy efficiently through a series of antenna complexes to the reaction center where charge separation occurs. Energy transfer in vivo is primarily monitored by measuring fluorescence signals from the small fraction of excitations that fail to result in charge separation. Here, we use two-dimensional electronic spectroscopy to follow the entire energy transfer process in a thriving culture of the purple bacteria, Rhodobacter sphaeroides . By removing contributions from scattered light, we extract the dynamics of energy transfer through the dense network of antenna complexes and into the reaction center. Simulations demonstrate that these dynamics constrain the membrane organization into small pools of core antenna complexes that rapidly trap energy absorbed by surrounding peripheral antenna complexes. The rapid trapping and limited back transfer of these excitations lead to transfer efficiencies of 83% and a small functional light-harvesting unit. During photosynthesis, energy is transferred from photosynthetic antenna to reaction centers via ultrafast energy transfer. Here the authors track energy transfer in photosynthetic bacteria using two-dimensional electronic spectroscopy and show that these transfer dynamics constrain antenna complex organization.